Análise do uso da linguagem em crianças com deficiência visual sob uma perspectiva funcional. - Oliveira, Jáima Pinheiro de (2004)
The importance of the language for the visual impairments children is unquestionable. Therefore, it is in function of it that they plan, modify or they improve their behavior. In the scientific field, it is discussed until the point the absence of the vision intervenes in its acquisition, development and use. The main objective of this study was to analyse the differences and similarities between the pragmatic performance of the language of visual impairments and sighted children in different contexts. Six preschoolers and their mothers had participated in the set of observations: two blind children; two visual impairments children; and two sighted children. The participants from Instituto dos Cegos do Brasil Central (MG) were chosen after a critical selection performed by clinical diagnostic and anamnese interviews with their mothers. Free and planned monitoring sections were performed in their homes and in the Instituto dos Cegos. In addition, the sections were taperecorded. The analyses of different situations were based on the functional use of the language, being considered communicative functions, as well as the ways used in the emissions. The results had indicated that the predominant way in the communication is the verbal one. The children with low vision capacity used more motor actions, because of the attempt to nominate them verbally, later. The blind children used more the verbal way in its communication, mainly to require information of the environment and after that to plan or to modify its behavior. In relation to the stimulation in their homes, it was possible to verify the use of materials adapted (ball-bell) by some mothers as well as alterations in the interaction between mother-child, which was evidenced mainly for low the frequency of communicative functions arisen from the children. The results of the study had important educational implications, mainly for the interventions with the family in their homes.